TBK1 and Flanking Genes in Human Retina - Fingert, John H. (2013)
PURPOSE: The gene that causes normal tension glaucoma (NTG) in a large pedigree was recently mapped to a region of chromosome 12q14 (GLC1P) that contains the genes TBK1, XPOT, RASSF3, and GNS. We sought to investigate the structure of the chromosome 12q14 duplication and explore the ocular expression of GLC1P locus genes. METHODS: The location of the chromosome 12q14 duplication in this pedigree was examined with fluorescent in situ hybridization (FISH) using probes for TBK1 and GNS. The expression pattern of XPOT, TBK1, RASSF3, and GNS was investigated with immunohistochemistry of human eyes. RESULTS: The karyotype of an NTG patient from pedigree GGO-414 was normal and FISH studies demonstrated that the duplicated DNA is organized as a tandem repeat on chromosome 12q14. Of the genes in or near the chromosome 12q14 duplication, TBK1 showed expression in the retina that is specific to the retinal ganglion cells and the retinal nerve fiber layer. Expression of RASSF3 and XPOT was relatively uniform throughout the retina, while GNS expression was expressed in a pattern consistent with Müller cells. CONCLUSIONS: Previous studies demonstrated that chromosome 12q14 duplications are associated with NTG inherited as an autosomal dominant trait. FISH studies now demonstrate that the duplicated segments are tandemly organized on chromosome 12q14 in close proximity. The specific expression of TBK1 in human retinal ganglion cells compared to the widespread pattern of expression of neighboring genes provides additional evidence that TBK1 is the glaucoma gene in the chromosome 12q14 duplication within the GLC1P locus.